The Integration and Development of EFL Classroom Materials Based on Local Culture: A Systematic Literature Review - Ni Nyoman Tantri; Made Hery Santosa (Universitas Pendidikan Ganesha, 2024)
This literature review focuses on the studies of the urgency of integrating and developing local culture-based material in English Foreign Language (EFL) classroom. The purpose of this study is to analyze information on the urgency of integrating and developing the local culture-based material in EFL classroom and find out the strategy of learning English along with local culture-based content. This study was a thorough review of the literature, assimilating both qualitative and quantitative steps. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Guidelines was used in this literature review. It reviews various aspects, such as the need analysis of local culture integration in EFL, various studies on developing local culture materials in some English language skills, and studying the impacts of developing local culture-based materials in Indonesian EFL classroom. A thorough comprehensive analysis was done by analyzing ten articles found both from national and international reputable journal. The result of the study showed that there is an evaluation on the need of the integration and development of EFL classroom based on local material, followed by developing the materials, and investigation toward the effectiveness of the material developed as further evaluation.